Penyuluhan dan Bimbingan Metode Perbaikan dan Perawatan Mesin Outboard pada Kapal Nelayan di Desa Pa’bentengang Kabupaten Maros - Syerly Klara; Faisal Mahmuddin .; Surya Hariyanto .; Rahimuddin .; A Haris Muhammad .; M Rusydi Alwi .; Ganding Sitepu .; Hasnawiyah H .; A Husni Sitepu .; Balqis Shintarahayu . (Faculty of Engineering UNHAS, 2022)
Increasing marine resources is one of the present government programs. To support this, it is necessary to increase human resources in coastal areas. One of the fundamental and important things is basic knowledge of machine repair and maintenance methods. The high cost of repairing and maintaining outboard engines is one of the major issues to fishermen, their lack of knowledge about engine repair and maintenance has resulted in them having to spend more money on it. This dedication activity was attended by 11 people from the “Sehati” fishing group. From the results of the counseling and guidance that has been carried out, 90% of fishermen are in the good category and plan to implement a schedule and how to maintain the fuel, lubricant and engine cooling water system. The remaining 10% of fishermen still do not understand the importance of the ship's outboard engine maintenance schedule, this is due to the low level of education so they still need time to learn the material that has been given. With many fishermen who are able to implement schedules and how to maintain the fuel, lubricant and engine cooling water system, the productivity and welfare of the fishing community increases, especially in the place where this activity is carried out, namely in Pa'bentengang village, Marusu District, Maros Regency.